Numerical modeling of implant surgery and rehabilitation of humerus bone fractures for the elderly patients - Batrakov, D.O.; Palamarchuk, V.V.; Tremtyachny, V.I. (Biophysical Bulletin, 2021)
Background: Implantation is becoming more widespread in such areas of modern medicine as orthopedics and traumatology. Due to the lack of an adequate substitute for natural bone, combined approaches are used. For older patients, the problem is exacerbated by a decrease in bone mineral density. When choosing a scheme for the surgical treatment of long bone fractures, preference is given to simple and maximally sparing approaches. In this regard, the main task of osteosynthesis is to provide optimal mechanical channels not only for the fracture healing process, but also to restore full functional capabilities in the future. The paper considers the urgent task of optimizing and increasing the efficiency of planning rehabilitation measures, including taking into account the individual characteristics of a particular patient, and the results are of fundamental and applied importance.Objectives: development of physical and mathematical models for modeling the stress-strain state of the elements of the musculoskeletal system to optimize the planning of bone surgeries when installing implants.Materials and methods. For the analysis, both specific clinical results and modern methods of computer modeling and processing of results were used. The advantage of physical and mathematical models based on the used finite element method is the possibility of optimizing the design of prostheses and reducing the problems caused by osteopenia.Results: To illustrate the proposed approach, a specific example of the treatment of a comminuted fracture of the humerus in an elderly patient is considered. To describe the physicomechanical properties of bone tissue, sets of standard data on the main characteristics of tissues and materials of implants such as elastic modulus and Poisson's ratio were used. As the bone grows together, simultaneously with a decrease in stresses, the difference between the stress on the entire structure and the stress on the bone decreases. This indicates that the bone begins to take on an increasingly significant relative part of the load, which should have a positive effect on its bone mineral density.Conclusions: The advantages of modeling using the finite element method and by non-invasive modeling of the work of the patient's musculoskeletal system with various variants of prostheses (implants) and the choice of the most optimal one are shown. It was found that the use of the Von Mises stress-strain state as a criterion for assessing the stress-strain state of the system gives effective assessments of the reliability of the structure and its elements.